Effects of the non-steroidal anti-inflammatory drug celecoxib on cholesterol containing distearoyl phosphatidylcholine membranes. Issue 3 (2011) - Sade Sade, Asli Asli; Banerjee Banerjee, Sreeparna Sreeparna; Severcan Severcan, Feride Feride
Abstract : The effects of different concentrations of celecoxib on the acyl chain order, dynamics and the hydration status of the head group and interfacial region of model membranes containing DSPC and cholesterol were investigated in detail using Fourier transform infrared spectroscopy. Our results reveal that regardless of the presence of cholesterol, celecoxib is able to alter the physical properties of membranes. It exerts opposing effects on membrane order at high and low concentrations and decreases membrane fluidity in the presence of cholesterol. An evidence of phase separation has also been observed. The decrease in membrane fluidity supports the hypothesis that celecoxib may induce changes in the activity of membrane bound enzymes through modulating physical properties of the membrane thereby contributing to its anticancer activity. A possible change in the location of celecoxib in DSPC membranes when cholesterol is present has also been proposed. These results clarify, to a certain extent, the molecular interactions of celecoxib with membrane systems and may additionally contribute to a better understanding of COX-2 independent mechanisms of celecoxib action.